Analysis of sintering behavior of alumina green bodies molded under a strong magnetic field based on master sintering curve theory. Issue 20 (15th October 2022) - Otsuka, Yuki; Yamamoto, Isao; Iijima, Motoyuki; Tatami, Junichi
Abstract: Understanding and controlling the anisotropic sintering shrinkage behavior of the green body in the strong magnetic field molding technique bring out the superior functions of ceramics. This study aimed to elucidate the sintering behavior of green bodies molded under a strong magnetic field using the master sintering curve (MSC) theory. Green bodies were prepared to obtain MSCs in the directions perpendicular and parallel to the applied magnetic field. A unique MSC of the alumina green bodies molded with and without a magnetic field was obtained using sintering shrinkage ratio estimated by various heating rates. The apparent activation energy of sintering in the direction perpendicular and parallel to the applied magnetic field was 663 kJ/mol, independent of the measured direction, which is higher than that without an applied magnetic field (562 kJ/mol). The (0001) planes of the sintered body obtained from the green body molded in the magnetic field were oriented perpendicular to the magnetic field, whereas the samples without a magnetic field were randomly oriented. Consequently, we found that the grain boundaries with high consistency in the sample applied to a magnetic field should increase the apparent activation energy because of its grain orientation. Highlights: Oriented and dense alumina ceramics were obtained by applying a magnetic field. A unique MSC was obtained for green bodies with and without magnetic field. Molding in the magnetic field resulted in higher activation energy of sintering. Highly consistent grain boundaries caused the higher activation energy.